2019
DOI: 10.1021/acsmacrolett.9b00133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polymerized Ionic Liquid Structure and Morphology on Shockwave Energy Dissipation

Abstract: The ability of nanosegregated polymerized ionic liquids (PILs) to dissipate shockwave energy is investigated for a series of imidazolium-based PILs with varying alkyl spacer length. The PILs are designed to have similar glass transition temperatures but different structures. X-ray scattering analysis reveals that each of the amorphous PILs exhibit distinct nanoscale structural heterogeneity, depending on the length of the chain spacer. We find that a higher structural heterogeneity, determined from the intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…The detailed procedure for PIL synthesis is shown in the Supporting Information (Figure S1), and the successful preparation of PIL was confirmed by 1 H NMR and FT-IR spectroscopy (Figure S2). As shown in Figure S2a, the peaks at 6.9, 7.1, and 7.4 ppm representing the protons at the imidazole moiety totally shifted to 7.8 ppm, standing for the protons at the imidazolium moiety in the 1 H NMR spectrum of PIL after in situ polycondensation, which confirmed the full polycondensation of the precursors for PIL …”
Section: Results and Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…The detailed procedure for PIL synthesis is shown in the Supporting Information (Figure S1), and the successful preparation of PIL was confirmed by 1 H NMR and FT-IR spectroscopy (Figure S2). As shown in Figure S2a, the peaks at 6.9, 7.1, and 7.4 ppm representing the protons at the imidazole moiety totally shifted to 7.8 ppm, standing for the protons at the imidazolium moiety in the 1 H NMR spectrum of PIL after in situ polycondensation, which confirmed the full polycondensation of the precursors for PIL …”
Section: Results and Discussionmentioning
confidence: 60%
“…As shown in Figure S2a, the peaks at 6.9, 7.1, and 7.4 ppm representing the protons at the imidazole moiety totally shifted to 7.8 ppm, standing for the protons at the imidazolium moiety in the 1 H NMR spectrum of PIL after in situ polycondensation, which confirmed the full polycondensation of the precursors for PIL. 34 FT-IR measurements of the electrolytes were also performed to investigate the interaction between [C 14 Mim][I] and PIL in PIL-ILC a (Figure S2, Supporting Information). No new peak and no chemical band shift were observed in the FT-IR spectrum of PIL-ILC a by comparing with those of PIL and ILC a , which suggested that the molecular assembly of PIL and ILC a in PIL-ILC a was mainly based on physical interactions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This mixing can also be inferred from the clear discrepancy in distance between the two carbon atoms bonded to terminal aromatic rings of a hard segment (≈ 3 nm) and the width of a hard domain ribbon. Furthermore, the experiments indicate that there is little or no crystallinity in polyurea [13,15], which likely helps to improve shock energy absorption [18].…”
Section: Introductionmentioning
confidence: 99%